The Effect of Audit Office-Size on Earnings Management: An Evidence from UK - FU, YIHAO (2017)
Earnings quality is concerned by information users such as shareholders and government regulators, and how to constrain earnings management has been widely discussed by previous researchers. From the view of auditors’characteristics, audit office size level could have an impact on earnings quality of clients. My study examines how the earnings quality vary from different audit office sizes base on the UK sample of listed companies from 2014-2016,by using Jones (1991) model to capture earnings management, I conclude that larger audit office size can help constrain earnings management and improve reporting reliability, and accumulated industry expertise for auditors also help improve earnings quality.